Arquitetura do medo em Fortaleza - Aragão, Antonio Caetano Teixeira Paz (2017)
We study in this research an Architecture of Fear in Fortaleza, an urban process, although in a different and less expressive way, has always existed in the cities, and that has recently been presented more explicitly in Brazilian cities that suffer from the problems of violence and fear. We present, in the first chapter, the conceptualization of the Architecture of the Fear that we investigate, its singularity as object of study, and the statement of the thesis presented here. In the second chapter, we deal with the fundamental questions of the research that we developed, in the search for situations that would show us the "limits" of where "differences" could arise, meetings and territorial constitution, knowledge associated with the problem and reasons for the construction of Architecture of Fear in Fortaleza. In the third chapter, we proceed to a complementary approach, where and when we will be identifying the boundaries (from the outside and the inside) in an analysis of urban micropolitics and processes of subjectivation, within the scope of the problem of fear construction, violence, the analyzed architecture and the city, more especially of the urban spaces that undergo interference of the implantation of the architecture of the bars and the walls that isolate, explain dichotomies: safe and insecure; private and public; rich and poor, good (citizens) and bad ("elements"), or in three words: segregation, self-segregation and fear. We conclude with a chapter that shows us that we are dealing with a theme in which we value, as a method of approach, studies of the relation of subjectivity to social exteriority that is of fundamental importance for understanding the present world, where the architecture of fear is inserted, but we also show that we are dealing here with processes that can be reopened, revised, from any place of time and space, without beginning, without teleology, but with the hope that the processes of homogenization of organisms can be broken, giving space to a field of immanence of desire, where creativity can flow to the benefit of better spaces of Brazilian architecture and cities.